Influence of Ti addition on fracture behaviour of HSLA steel using TIG melting technique - M. H. A, Musa; Maleque, Md. Abdul; Ali, M. Y. (IOP Publishing, 2017)
The welding process is a critical stage in the production of structural parts and the microstructure and mechanical properties of the welded joints must be appropriate in order to guarantee the reliability and durability of the components. The fracture toughness behaviour, which accounts for the residual strength of the component in the presence of flaws or cracks, is one of the most important properties to be evaluated in terms of microstructure and mechanical properties. In this present study, the surface of high strength low alloy (HSLA) steel was surface modified with the preplacement of pure Titanium (Ti) powder using a tungsten inert gas (TIG) arc heat source, at 100 ampere current with a voltage 30 V and a constant traversing speed of 1.0 mm/s using Argon shielded gas. The effect of preplaced Ti powder on the strength and toughness properties of the modified HSLA steel surface was investigated. The results indicated that the tensile and yield strength of HSLA steel decreased by ~12% and ~14%, respectively. While the impact toughness increased by ~33% and the ductility decreased by ~50%. The fractography analysis results by scanning electron microscopy (SEM) were also presented in this paper.